Vermicompost – A Soil Conditioner cum Nutrient Supplier - K, Tharmaraj. (International Journal of Pharmaceutical & Biological Archive, 2012)
ABSTRACT Composting, generally defined as the biological aerobic transformation of an organic by-product into a different organic product that can be added to the soil without detrimental effects on crop growth. Vermicomposting is a simple biotechnological process of composting, in which certain species of earthworms are used to enhance the process of waste conversion and produce a better end product. Vermicompost is derived by rearing worms on organic work mixed with cattle dung. It contains plant nutrient like N, P, K, Ca, Mg, Fe, Mn and Zn which has a positive effect on the plant growth, yield, soil fertility and soil microbes. This present review paper revealed the various dynamic of the soil – plant relationship with special emphasis on vermicompost. This review assesses the following topics: effect of vermicompost on soil property and application of vermicompost.